Business process management with JBoss jBPM a practical guide for business analysts : develop business process models for implementation in a business process management system - Cumberlidge, Matt.; Safari eBooks (Birmingham, U.K. : Packt Pub., 2007)
"Businesses have always tried to manage their processes, but software such as jBPM brings the methodology and management theory to practical life. This book shows business analysts how to model business processes in JBoss jBPM and use these models to generate a fully-functioning workflow application. The book shows how business analysts can use the tools to build a solution without the need for Java coding expertise. It also introduces more advanced functionality that can be implemented by Java developers in partnership with the BA"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Reengineering (Management); Management -- Computer programs; JBoss; Electronic books